Discovery of novel arylamide derivatives containing piperazine moiety as inhibitors of tubulin polymerisation with potent liver cancer inhibitory activity - Xiao-Yi Shi; Huang Jiao; Jia-Kai Zhang; Xin-Yi Tian; Dan-Feng Guo; Jie Gao; Mei-Qi Jia; Jian Song; Sai-Yang Zhang; Xiang-Jing Fu; Hong-Wei Tang (Taylor & Francis Group, 2023)
In this work, a series of novel arylamide derivatives containing piperazine moiety were designed and synthesised as tubulin polymerisation inhibitors. Among 25 target compounds, compound 16f (MY-1121) exhibited low nanomolar IC50 values ranging from 0.089 to 0.238 μM against nine human cancer cells. Its inhibitory effects on liver cancer cells were particularly evident with IC50 values of 89.42 and 91.62 nM for SMMC-7721 and HuH-7 cells, respectively. Further mechanism studies demonstrated that compound 16f (MY-1121) could bind to the colchicine binding site of β-tubulin and directly act on β-tubulin, thus inhibiting tubulin polymerisation. Additionally, compound 16f (MY-1121) could inhibit colony forming ability, cause morphological changes, block cell cycle arrest at the G2 phase, induce cell apoptosis, and regulate the expression of cell cycle and cell apoptosis related proteins in liver cancer cells. Overall, the promising bioactivities of compound 16f (MY-1121) make the novel arylamide derivatives have the value for further development as tubulin polymerisation inhibitors with potent anticancer activities.